EFFECT OF B4C ADDITION ON THE MICROSTRUCTURE, HARDNESS AND DRY-SLIDING-WEAR PERFORMANCE OF AZ91 COMPOSITES PRODUCED WITH HOT PRESSING - Öge, Tuba Özdemir; Öge, Mecit; Yılmaz, Volkan Murat; Yılmaz, Volkan Murat; Öge, Tuba Özdemir; Özdemir, Firdevs Banu; Öge, Mecit; Yılmaz, Volkan Murat; Öge, Tuba Özdemir; Öge, Mecit (Inst Za Kovinske Materiale I In Tehnologie, 2019)
AZ91-B4C composites were fabricated with varying reinforcement ratios (5 w/%, 10 w/%. 20 w/% and 50 w/%) B4C) via powder metallurgy and hot pressing to examine their microstructure, hardness and dry-sliding-wear performance. Powder compositions were verified with XRD and the microstructure of the sintered composites was evaluated using SEM (Scanning Electron Microscope) and EDS analyses. Hardness measurements and dry-sliding-wear tests were performed to evaluate the effect of reinforcement addition on the hardness and wear performance of the fabricated composites. Hot pressing of the composite with 50 w/% B4C required a significantly higher sintering pressure at the same sintering temperature. Increasing the B4C addition resulted in increased hardness values for all the composites. whereas the lowest worn volume and coefficient of friction were obtained with 10 w/% B4C.
Keywords: Metal-Matrix Composites; Particle Size; Boron Carbide; Az91; Material Characterization; Sem; Hardness; Dry Sliding Wear